Legal Reform on Rock Mining Governance: the Dual Liability Model For Protecting Environmental Rights in Palu–Donggala - Rosdian Rosdian; Sulbadana Sulbadana; Agus Lanini; Suardi Suardi; Supriyadi Supriyadi (Fakultas Hukum Universitas Lampung, 2025)
Addresses the urgent need for a legal framework to regulate rock mining in the geologically fragile Palu–Donggala coastal region, where exploitation often conflicts with the constitutional Right to a Good and Healthy Environment (Article 28H of the 1945 Constitution). It examines the failure of local governments to fulfill their obligation to protect citizens’ rights and the ineffectiveness of existing sanctions. Using a normative legal (juridical-normative) method with constitutional, progressive human rights, and conceptual approaches, the research analyzes ius constitutum and ius constituendum through doctrinal interpretation. The research formulates the Dual Liability Model, which holds corporations financially accountable for ecological losses and local governments legally responsible for rights violations. This model promotes the use of Environmental Carrying Capacity (ECC) as an absolute veto in licensing, ensuring stronger environmental governance and effective restoration of citizens’ rights in disaster-prone regions..